URGENSI IMPLEMENTASI LAPORAN BERKELANJUTAN (SUSTAINABILITY REPORTS) DI PERGURUAN TINGGI - Miqdad, Muhammad; Izzalqurny, Tomy Rizky (BISMA: Jurnal Bisnis dan Manajemen, 2019)
The purpose of this study is to analyze the urgency of implementing sustainability reports that supports Sustainable Development Goals (SDGs) at the higher education level. This research uses a qualitative descriptive method with the literature study and case study approaches. Data from the literature study were taken from various sources, i.e., research articles, books, websites, and other scientific references. Primary data from the case study were sourced from the results of the survey and interview at one of the state universities in Indonesia. The data processing and analysis include data reduction, data presentation, and conclusion making. Results showed that various organizations have produced sustainability reports regularly. This finding implied that for higher education institutions (especially the university service agencies and legal entity for state universities), the regular publishing of sustainability reports is a manifestation of the transparency of organizational actions towards the environment and society and that it could be a good example for other organizations. Therefore, higher education institutions can have a significant role as the main pillar to support the implementation of SDGs programs in all sectors in Indonesia.